2017
DOI: 10.1016/j.jpsychires.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Receptiveness to participation in genetic research: A pilot study comparing views of people with depression, diabetes, or no illness

Abstract: Background Genetic research in human health relies on the participation of individuals with or at-risk for different types of diseases, including health conditions that may be stigmatized, such as mental illnesses. This preliminary study examines the differences in attitudes toward participation in genetic research among individuals with a psychiatric disorder, individuals with a physical disorder, and individuals with no known illness. Methods Seventy-nine individuals with a history of diabetes or depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…In addition, persons were willing to participate in a study related to Alzheimer's disease, a disorder that currently has a poor prognosis. These results are consistent with previous reports that participants would be interested in genetic research for complex diseases such as heart disease (Walker et al 2014), diabetes, and depression (Roberts and Kim 2017). Further qualitative research could elucidate the underlying causes of African Americans' willingness to participate in genetic research.…”
Section: Attitudessupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, persons were willing to participate in a study related to Alzheimer's disease, a disorder that currently has a poor prognosis. These results are consistent with previous reports that participants would be interested in genetic research for complex diseases such as heart disease (Walker et al 2014), diabetes, and depression (Roberts and Kim 2017). Further qualitative research could elucidate the underlying causes of African Americans' willingness to participate in genetic research.…”
Section: Attitudessupporting
confidence: 91%
“…In addition, advancements in these fields will be incomplete without individuals with or at risk for different types of diseases, including disorders influenced by varying genes and environmental factors, and conditions associated with stigma. Previous studies have indicated, for instance, that individuals with and without a medical history of a stigmatizing disease expressed a willingness to participate in real time and future genetic research (Laegsgaard et al 2009;Roberts and Kim 2017). For psychiatric disorders, which are arguably some of the most stigmatizing, intentions to test were positively associated with parental status, trust in researchers, and an expectation that knowledge would increase one's preparedness related to health risk.…”
Section: Introductionmentioning
confidence: 99%
“…A majority of participants with different psychiatric diagnoses expressed intention to test for genetics regardless of treatment possibilities (Laegsgaard, Kristensen, & Mors, 2009). Our prior work documented that individuals with and without a history of mental illness viewed genetic and medical research favorably and indicated that they would likely participate in genetic research now and even in the future (Roberts & Kim, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, some have investigated public interest in predictive genetic testing (Wilde et al 2010), while many more have examined the concerns, attitudes, and knowledge of health professionals in particular, who are tasked to use genetic information with their patients (Klitzman et al 2014, Wilde et al 2014, Salm et al 2015). Fewer studies have assessed the concerns of at-risk individuals, including vulnerable populations such as youth and pregnant women (Inglis et al 2018, Laegsgaard, Kristensen, & Mors, 2009), and even fewer have sought to compare potential participants’ views of the societal importance of genetic research on mental disorders with those of their healthy counterparts (Laegsgaard and Mors 2008, Roberts and Kim 2017). Still, little empirical work has investigated the attitudes of potential participants in psychiatric genetics research and the views of those stakeholders who might choose to enroll in genetic studies (Laegsgaard, Kristensen, & Mors, 2009).…”
mentioning
confidence: 99%
“…The importance and value of biobanking in health research has been growing during the last decades mostly due to genetic knowledge advancements and technology innovation. In the context of psychiatric disorders, research based on the use of biological material stored in biobanks together with health information and clinical data may produce new strategies for prevention, early detection, accurate diagnoses, and tailored treatments (1). Among psychiatric disorders, major depressive disorder (MDD) is the most frequent, persistent and debilitating disorder occurring in the general population, with an estimated lifetime prevalence of approximately 12.8% in Europe (2).…”
Section: Introductionmentioning
confidence: 99%